An annotated catalogue of the Membracidae types in the Museu de Zoologia da Universidade de São Paulo, Brazil (Hemiptera: Auchenorrhyncha: Cicadomorpha) - Evangelista, Olivia; Dos Santos, Guilherme Ide Marques; Lamas, Carlos Einicker (Zootaxa, 2014)
Here presented is an annotated catalogue of the Membracidae types deposited at the Museu de Zoologia da Universidade de São Paulo (MZSP), with information on 106 primary types and 171 secondary types. These type specimens represent 82 nominal species currently classified in 8 treehopper subfamilies and 17 tribes. According to our estimates, at least 10 primary types and 44 secondary types are missing in the collection. A comprehensive list of literature sources, taxonomic remarks, label data and descriptions on the state of preservation of specimens are given.